TV digital interativa e hipermídia: jogos e narrativas interativas na TVi - Ribeiro, João Henrique Ranhel (2005)
This thesis exposes a survey of new theories, researches and new approaches in the areas of narratology and ludology. It also exposes investigations on feasibility of using the knowledge acquired in such areas in developing new interactive contents for Digital Interactive TV (iTV). Initially the text shows an objective description of technical and operational aspects of the iTV. In the sequence, the narratologists and ludologists propositions are discussed. Narratology is a line of thought that studies the possibilities of interactive dramas a narrative structure in which the user can immerse as a character that he/she plays in first-person. Ludology is a line of thought that studies computer games virtual environments and worlds where the user can simulate, explore, face challenges, etc. The present research tries to survey the most relevant theoretical approaches and propositions from both areas narratology and ludology. Based on such propositions and theories we evaluate the possibility of introducing interactive dramas, new forms of games and new interactive programs in the iTV environment.